Strategi Komunikasi Persuasif Lurah Taba Lestari Dalam Meningkatkan Kesadaran Pola Hidup Sehat Di Era New Normal - Muhammad Randicha Hamandia (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
The purpose of this study is to find out how the image of awareness of the healthy lifestyle of the Taba Lestari village community before a persuasive communication strategy is applied, to find out how the Taba Lestari village head's persuasive communication strategy is to increase awareness of a healthy lifestyle in the new normal era, and to find out how the picture of awareness pattern healthy life of the Taba Lestari village community after the persuasive communication strategy was applied. The theory used in this research is the theory of persuasive communication strategy by Melvin L. Defluer and Sandra J. Ball-Roceach. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results of research that have been carried out in describing the awareness of people's lifestyles before the existence of a persuasive communication strategy, people have implemented a healthy lifestyle, but people are not fully aware of it. In psychodynamic strategies that involve emotional and cognitive factors in society in persuasion. Sociocultural strategies take advantage of environmental factors rather than society. The meaning construction strategy focuses more on providing understanding to persuade by manipulating words and attracting attention without changing a meaning. An illustration of awareness of a healthy lifestyle after the implementation of persuasive strategy communication that is carried out to increase awareness of a healthy lifestyle in the new normal era.